IDENTIFICATION OF INDIVIDUALS BASED ON EXTERNAL APPEARANCE FEATURES: FORENSIC REGISTRATION SYSTEMS - Mamanarov Xaitmurat, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the forensic identification of individuals based on external appearance features and the role of forensic registration systems in modern criminalistics. The study analyzes the scientific foundations of anthropometric, morphological, and descriptive classification techniques and evaluates the integration of biometric technologies—such as facial recognition algorithms, 3D modeling, dermatoglyphics, and photographic registration—into traditional forensic practice. Using comparative analysis of classical criminological theories, contemporary biometric research, and practical case materials, the article outlines the capacities and limitations of appearance-based identification in investigative processes. The results highlight the necessity of methodological rigor, multimodal biometric verification, and consistently updated forensic registries to ensure reliability in offender identification, missing persons searches, and postmortem examinations.